2001
DOI: 10.1103/physrevlett.86.5767
|View full text |Cite
|
Sign up to set email alerts
|

NMR Evidence for Coexistence of Superconductivity and Ferromagnetic Component in Magnetic SuperconductorRuSr2YCu2O8<

Abstract: From Ru- and Cu-NMR studies, we present evidence for coexistence of superconductivity and ferromagnetism in a cuprate superconductor RuSr2YCu2O8 (RuY1212). The observation of a large enhancement of a radio-frequency field for the Ru-NMR signal at zero field reveals the existence of a ferromagnetic (FM) component in the ordered RuO2 plane below a Curie temperature of TM = 150 K. Just below the onset temperature of superconductivity T(onset)c = 45 K, a remarkable decrease of the nuclear spin-lattice relaxation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
92
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 19 publications
14
92
3
Order By: Relevance
“…The zero-field NMR data suggest that the aligned moment of Ϸ1.6 B /Ru should be perpendicular to the c axis instead and that the FM component should be a large part of the moment. 6 While at least two other NPD studies claim similarly negligible FM components, 7,8 both the large FM moment and the perpendicular spin direction were confirmed by independent NMR measurements. 9 These conflicts will be difficult to reconcile, in our opinion, if these ruthenocuprates are microscopically homogeneous.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The zero-field NMR data suggest that the aligned moment of Ϸ1.6 B /Ru should be perpendicular to the c axis instead and that the FM component should be a large part of the moment. 6 While at least two other NPD studies claim similarly negligible FM components, 7,8 both the large FM moment and the perpendicular spin direction were confirmed by independent NMR measurements. 9 These conflicts will be difficult to reconcile, in our opinion, if these ruthenocuprates are microscopically homogeneous.…”
Section: Introductionmentioning
confidence: 79%
“…[1][2][3][4][5][6] Even in the relatively simple case of Ru1212, a large discrepancy exists. A NPD investigation reported that the Ru spins ordered antiferromagnetically ͑AFM͒ along the c axis with a rather stringent upper limit of (0.1,0.2) B /Ru at Hϭ0 and 7 T, respectively, for the ferromagnetic ͑FM͒ components of Ru.…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of bulk superconductivity at low temperatures in Ru-1212 was initially criticised [11] which was later refuted [12,13]. Also not all single phase Ru-1212 exhibit the co-existence of superconductivity and magnetism [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an additional complication in that the crystallite domain size is small and there are coherent rotations of the RuO 6 octahedra about the c-axis leading to a superstructure and subdomains of 5 nm to 20 nm in diameter [5,8]. It has been suggested on the basis of transport, heat capacity and microwave measurements that the electronic behavior of RuSr 2 RCu 2 O 8 is similar to an underdoped HTSC [6,18] However, nuclear magnetic resonance (NMR) measurements have been interpreted in terms of RuSr 2 RCu 2 O 8 being comparable to an optimally doped HTSC [24].…”
Section: Introductionmentioning
confidence: 99%